The Rise of New Banks: Disrupting the Traditional Banking Landscape - Gupta, Rahul (Journal of Global Economy, Business and Finance, 2024)
Neobanks are online - only, digital - only financial institutions. They are, to put it simply, non - existent. Customers may need to invest a significant amount of time and effort in typical bank transactions. Neobanks add an immersive digital layer to traditional banking, promising a smooth online experience. [1] Neo banks frequently provide a comprehensive array of financial services that may be accessed via their mobile applications or websites, such as checking and savings accounts, loans, payments, investments, and budgeting tools. Neo banks place a high priority on data privacy and security. [2]. Nonetheless, new banks continue to face difficulties with regulatory compliance. Opportunities might be found in developing user experience technology and providing creative, customised financial products. Neo banks are becoming more and more popular, but traditional banks won't likely disappear anytime soon because both may survive and meet distinct client needs in the changing banking environment. [2]